KEDISIPLINAN ATLET BOLA VOLI DAN BOLA BASKET PADA MASA ADAPTASI KEBIASAAN BARU DI KABUPATEN BULELENG BALI - Wijaya, Made Agus; Permana, W Gde Gandhi; Adi, I Putu Panca (Universitas Negeri Surabaya, 2022)
Physical activity during the Covid-19 pandemic still needs to be done so that the body is healthy and fit. The purpose of this study was to obtain empirical data on the level of discipline of volleyball and basketball athletes during the adaptation period of new habits in Buleleng Regency-Bali. This descriptive study uses simple random sampling, the number of samples is 48 volleyball athletes and 60 basketball athletes. The research instrument is in the form of a closed questionnaire in a google form. Data analysis used quantitative-qualitative descriptive. The results showed: 1) volleyball athletes who were in the very disciplined category were 16 people (49%), the discipline category was 25 people (52%), and the moderately disciplined category was 7 (15%). The average score of volleyball athlete respondents reached 99.31, and 2) basketball athletes in Buleleng Regency included in the very disciplined category as many as 29 people (48%), the discipline category amounted to 24 people (40%), the moderately disciplined category reached 7 people (12 %). Based on data analysis and discussion, the conclusions of this study are: 1) the level of discipline of volleyball athletes in Buleleng Regency is included in the discipline category, and 2) the discipline level of basketball athletes is included in the discipline category. It is recommended to the people of Buleleng Regency to continue to do physical activity by implementing strict health protocols, taking regular breaks and maintaining a healthy body.